The correlations between optical/UV broad lines and X-ray emission for a large sample of quasars. Issue 1 (6th December 2019) - Timlin, John D; Brandt, W N; Ni, Q; Luo, B; Pu, Xingting; Schneider, D P; Vivek, M; Yi, W
ABSTRACT: We present Chandra observations of 2106 radio-quiet quasars in the redshift range 1.7 ≤ z ≤ 2.7 from the Sloan Digital Sky Survey (SDSS), through data release 14 (DR14), that do not contain broad absorption lines in their rest-frame ultraviolet (UV) spectra. This sample adds over a decade worth of SDSS and Chandra observations to our previously published sample of 139 quasars from SDSS DR5 that is still used to correlate X-ray and optical/UV emission in typical quasars. We fit the SDSS spectra for 753 of the quasars in our sample that have high-quality (exposure time ≥ 10 ks and off-axis observation angle ≤ 10 arcmin) X-ray observations, and analyse their X-ray-to-optical spectral energy distribution properties (αox and Δαox ) with respect to the measured C iv and Mg ii emission-line rest-frame equivalent width (EW) and the C iv emission-line blueshift. We find significant correlations (at the ≥99.99 per cent level) between αox and these emission-line parameters, as well as between Δαox and C IV EW. Slight correlations are found between Δαox and C IV blueshift, Mg II EW, and the C IV EW to Mg II EW ratio. The best-fitting trend in each parameter space is used to compare the X-ray weakness (Δαox ) and optical/UV emission properties of typical quasars and weak-line quasars (WLQs). The WLQs typically exhibit weaker X-ray emission than predicted by the typical quasar relationships. The best-fitting relationships for our typical quasars are consistent with predictions from the disc–wind quasar model. The behaviour of the WLQs compared to our typical quasars can be explained by an X-ray 'shielding' model.